Correlation between attention deficit/hyperactivity disorder and chronic pain: a survey of adults in Japan - Satoshi Kasahara; Takahiko Yoshimoto; Hiroyuki Oka; Naoko Sato; Taito Morita; Shin-Ichi Niwa; Kanji Uchida; Ko Matsudaira (Scientific Reports)
Abstract This cross-sectional epidemiological internet survey assessed whether attention deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) symptoms are associated with pain chronicity and intensity and explored the relationship between developmental disorder symptoms and pain. Participants were 4028 adults aged 20–64 years who experienced pain, assessed using an 11-point numerical rating scale (NRS), in any body part in the previous 4 weeks. ADHD and ASD symptoms were assessed using the Adult ADHD Self-Report Scale (ASRS) and autism spectrum quotient, respectively. Problems with mental health (PMH) were assessed using the shortened Profile of Mood States. Pathway analyses were performed to examine the association between ADHD symptoms and pain. The chronic pain symptoms (CP) group (N = 1465) scored higher than the non-CP group (N = 2563) for all ASRS variables. ASRS positivity was associated with CP symptoms and increased with increasing NRS score; the CP group showed particularly high positivity (38.3%) with extreme pain. ADHD symptoms were more strongly associated with CP symptoms and intensity than was PMH (0.26 vs. 0.09). ADHD symptoms, but not ASD symptoms, were associated with CP symptoms. ADHD medications reportedly improve coexisting CP; therefore, ADHD screening and treatment may be important for patients with CP, especially those with extreme pain.